Abundance changes in orb-weaver spider communities at the edge of the Argiope bruennichi expansion range - Wawer, Wioletta; Wytwer, Jolanta (Zootaxa, 2020)
Expanding range is an inherent feature of any species and may be caused by climate change, destruction or other change of habitat, or lack of natural enemies. In a new habitat the species may be neutral, or as predator it can displace related species through competition. A strong expansion to northern Europe was observed in the thermophilous spider species Argiope bruennichi. The species doubled its range in Poland during the 1990s and its impact on native species was not investigated so far. In this article, the results of studies about A. bruennichi number (density) and its contribution in orb-weaver spider communities are analysed. We also try to determine the impact of newly occurring species on the local araneofauna.